2011
DOI: 10.3238/arztebl.2011.0415
|View full text |Cite
|
Sign up to set email alerts
|

Uncomplicated Urinary Tract Infections

Abstract: The new S3 guideline on uncomplicated UTI incorporates a forward-looking approach to the use of antibiotics in treating this common type of infection. It is intended to bring about a sustained improvement in the quality of care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
54
0
15

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(70 citation statements)
references
References 25 publications
1
54
0
15
Order By: Relevance
“…Integrons are transferable genetic elements capable of expressing multiple resistance genes in cassette structures and are strongly associated with multidrug resistance (33). Concerns over increased resistance and the collateral effects of TMP/SMX use has led to the removal of TMP/SMX as a recommended agent from some guidelines (35). However, a recent systematic review did not find an increase in bacterial resistance to other antimicrobial classes with the use of TMP/SMX as prophylaxis in patients with HIV (29).…”
Section: Discussionmentioning
confidence: 98%
“…Integrons are transferable genetic elements capable of expressing multiple resistance genes in cassette structures and are strongly associated with multidrug resistance (33). Concerns over increased resistance and the collateral effects of TMP/SMX use has led to the removal of TMP/SMX as a recommended agent from some guidelines (35). However, a recent systematic review did not find an increase in bacterial resistance to other antimicrobial classes with the use of TMP/SMX as prophylaxis in patients with HIV (29).…”
Section: Discussionmentioning
confidence: 98%
“…These agents account for 8-10% of antibiotic prescriptions in Germany; in the last decade, rates of resistance to them have risen as well (3,4). In 2010, the S3 guideline of the Association of Scientific Medical Societies in Germany (AWMF) for uncomplicated UTI no longer recommended cotrimoxazole as a drug of first choice for this indication, because of increasing resistance (5). Rather, the new recommendation is for fosfomycin-trometamol and nitrofurantoin as drugs of first choice for this indication in Germany (and also pivmecillinam outside Germany), with fluoroquinolones as second-line agents.…”
mentioning
confidence: 99%
“…Recent studies with patients with uncomplicated cystitis, however, showed a general increase in TMP and fluoroquinolone resistance (3,9). Current guidelines for the treatment of uncomplicated UTI no longer recommend TMP or TMP-SMX as first-line agents if the regional resistance rate against TMP is higher than 20% (10)(11)(12). In the past, fluoroquinolones have also been recommended as first-line treatment for uncomplicated cystitis (4).…”
mentioning
confidence: 99%